2008
DOI: 10.1038/sj.bjc.6604474
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relationship between expression of hypoxia inducible factor 1α (HIF-1α) and the pro-apoptotic protein Bid in ex vivo colorectal cancer

Abstract: Hypoxia inducible factor 1 (HIF-1) represses the transcription of pro-apoptotic bid in colorectal cancer cells in vitro. To assess the clinical relevance of this observation, HIF-1a and Bid were assessed in serial sections of 39 human colorectal adenocarcinomas by immunohistochemistry. In high HIF-1a nuclear-positive cell subpopulations, there was a significant reduction in Bid expression (ANOVA, P ¼ 0.04). Given the role of Bid in drug-induced apoptosis, these data add impetus to strategies targeting HIF-1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Specifically, HIF-1 can downregulate pro-apoptotic Bid, the reversal of which is associated with enhanced chemotherapy response (Brown et al, 2006). The reciprocal relationship between HIF-1a and Bid expression is maintained in clinical samples of CRC, supporting its potential importance (Seenath et al, 2008). With current interest in the development of HIF-targeting agents as novel cancer therapies, these data would support their exploitation in combination with standard chemotherapy to enhance the treatment response in CRC.…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, HIF-1 can downregulate pro-apoptotic Bid, the reversal of which is associated with enhanced chemotherapy response (Brown et al, 2006). The reciprocal relationship between HIF-1a and Bid expression is maintained in clinical samples of CRC, supporting its potential importance (Seenath et al, 2008). With current interest in the development of HIF-targeting agents as novel cancer therapies, these data would support their exploitation in combination with standard chemotherapy to enhance the treatment response in CRC.…”
Section: Discussionmentioning
confidence: 86%
“…The relationship between IR and IGF-IR expression was determined in serial tumour sections from 17 patients with colonic adenocarcinomas immune-stained as described previously in our laboratory ( 34 ). Stained slides were scanned using a Mirax SCAN automated slide scanning system (Zeiss).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in high HIF-1α nuclear-positive cell subpopulations of 39 human colorectal adenocarcinomas, there was a significant reduction in Bid expression. (30) Many previous studies by us have shown that ST13 gene expression levels are significantly decreased in primary colorectal cancers compared with adjacent mucosal tissues. (18,31) It raises the question of whether the low expression of ST13 is due to hypoxia in colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%